Project-Based Learning for Spiritual Competence in Islamic Religious Education - Pawit Rohmat Cahyono; Robingun Suyud El Syam; Muhtar Sofwan Hidayat (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The growing demand for holistic education in the era of Industry 4.0 and Society 5.0 requires Islamic Religious Education (PAI) to foster not only cognitive mastery but also students’ spiritual competence. However, instructional practices in many PAI classrooms remain predominantly lecture-centered and insufficiently structured to facilitate systematic value internalization. This conceptual study aims to develop a theoretically grounded framework that aligns Project-Based Learning (PjBL) with processes of spiritual competence development in PAI. Employing an integrative literature review of contemporary scholarship (2015–2025), the study synthesizes perspectives from Islamic educational philosophy, experiential learning theory, and transformative learning theory. The findings indicate that spiritual competence comprises transcendental awareness, value appreciation, and moral–behavioral actualization. Furthermore, the stages of PjBL—problem identification, planning, implementation, and reflection—can be systematically mapped onto progressive processes of spiritual formation when guided by explicit ethical orientation and reflective practice. The study contributes by reconceptualizing PjBL as spiritual pedagogy rather than merely an active-learning strategy. Although conceptual in nature and not empirically tested, the proposed framework provides theoretical advancement and practical direction for PAI educators seeking to design experience-based spiritual learning. Future empirical studies are recommended to validate the framework across diverse educational contexts.